PRICE VOLATILITY OF RED CHILI PEPPERS IN CENTRAL JAVA - Eka Nurjati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Red chili peppers are an essential commodity because it affects inflation. Central Java is a province of one of the main producers of red chili peppers in Indonesia. Yet, the production and land area are decreasing in the period 2017-2019. The research was carried out to analyze the volatility of producer prices and consumer prices of red chili peppers. Based on the research results, it could be formulated the strategy to stabilize the price of red chili peppers in Central Java. This research used secondary data which was time-series data of monthly consumer price and producer price of red chili from 2006 to 2018. The result showed that only consumer price experienced the volatile, while the producer price had no volatility. The volatility of red chili peppers in the future would be lower, but the shock on the variant of price would occur for a long time. By following the research results, the strategy to stabilize the price of red chili peppers, i.e. dissemination of innovative technology to reduce the crop failure at the off-season, management of crop pattern, development the win-win solution of partnership and stakeholder system, development of logistic management, development of distribution systems, development the cold storage, dissemination of post-harvest technology for dry chili, and restriction of chili import.